ASYMPTOTIC EVALUATION OF PARAMETER-DEPENDENT INTEGRALS - Umirzakova Iroda; Komilov Abdulaziz (Journals Park Publishing, 2022)
This thesis presents the methods of calculating integrals that are approximate, but the calculation of their value is quite complicated.
Keywords: parameter-dependent integral, asymptotic estimation, Taylor series, Euler integrals.